ANALISIS K-MEDOIDS CLUSTERING PADA EPISENTRUM GEMPA BUMI DI PROVINSI SUMATERA BARAT DAN SEKITARNYA - Jeri Jefrianto; Devni Prima Sari (Journal of Mathematics UNP, 2022)
Sumatra is located along the confluence line of the Indo-AustralianPlate and the Eurasian plate, which has high seismic activity. Theisland of Sumatra is prone to earthquakes which pose a considerabledanger, and one of the provinces on this island that is prone toearthquakes is the Province of West Sumatra. So it is necessary tostudy each earthquake characteristic in the Province of West Sumatraand its surroundings using K-Medoids Clustering analysis.Earthquake data used is tectonic earthquake data from December 1970to September 2021 with attributes: latitude, longitude, and magnitude.In this study, several clusters were tried, namely K=2, K=3, K=4, andK=5 using the Euclidean Distance. The most optimum cluster is K=2of 0.448072 using the Silhouette coefficient validation test, theepicenter was at 99.290E and -1.050S with a magnitude of 5.38 on theSR for the first group and the second group produced an epicenter at101.150E and -3.440S with a magnitude of 5.36 SR.